Provider Visual Attention Correlates With the Quality of Pediatric Resuscitation: An Observational Eye-Tracking Study - Gröpel, Peter; Wagner, Michael; Bibl, Katharina; Schwarz, Hannah; Eibensteiner, Felix; Berger, Angelika; Cardona, Francesco S. (Frontiers in Pediatrics, 2022)
Background: Eye-tracking devices are an innovative tool to understand providers’ attention during stressful medical tasks. The knowledge about what gaze behaviors improve (or harm) the quality of clinical care can substantially improve medical training. The aim of this study is to identify gaze behaviors that are related to the quality of pediatric resuscitation. Methods: Forty students and healthcare providers performed a simulated pediatric life support scenario, consisting of a chest compression task and a ventilation task, while wearing eye-tracking glasses. Skill Reporter software measured chest compression quality and Neo Training software measured ventilation quality. Main eye-tracking parameters were ratio (the number of participants who attended a certain area of interest [AOI]), dwell time (total amount of time a participant attended an AOI), the number of revisits (how often a participant returned his gaze to an AOI), and the number of transitions between AOIs. Results: The most salient AOIs were infant chest and ventilation mask (ratio = 100%). During CC task, 41% of participants also focused on ventilation bag and 59% on study nurse. During ventilation task, the ratio was 61% for ventilation bag and 36% for study nurse. Percentage of correct CC rate was positively correlated with dwell time on infant chest (p = 0.044), while the overall CC quality was negatively correlated with dwelling outside of pre-defined task-relevant AOIs (p = 0.018). Furthermore, more dwell time on infant chest predicted lower leakage (p = 0.042). The number of transitions between AOIs was unrelated to CC parameters, but correlated negatively with mask leak during ventilations (p = 0.014). Participants with high leakage shifted their gaze more often between ventilation bag, ventilation mask, and task-irrelevant environment. Conclusions: Infant chest and ventilation mask are the most salient AOIs in pediatric basic life support. Especially the infant chest AOI gives beneficial information for the resuscitation provider. In contrast, attention to task-irrelevant environment and frequent gaze shifts seem to harm the quality of care.